Comprehensive review of the human body communication system for wireless body area network applications - Chaitra Soppinahally Nataraju; Desai Karanam Sreekantha; Kanduri V S S S S Sairam (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2023)
The body area networks (BAN) structure is one of the advancements in health monitoring innovations and the sharp rise in healthcare demand. With the help of a network of constantly running sensors, BAN technology aims to monitor vital physiological and physical features like accessibility, respiration, and blood sugar levels. The achievement of BAN technology depends on wireless communication since it gives the user flexibility and versatility. Most BAN solutions have effectively employed radio frequency (RF) wireless technology, although these systems are battery-intensive, prone to electromagnetic interference, and have security weaknesses. The human body is the signal transmission medium in the alternative wireless communication technology called human body communication (HBC). HBC possesses traits that could logically deal with the problems with RF for wireless body area networks (WBAN) technology. This overview looks at the ongoing research in this field and highlights the principles of the HBC, the most recent studies of HBC, human body coupling approaches, the designs of HBC transceivers, and the unresolved research issues. HBC provides promising future possibilities for making WBAN technologies more useful.